A focus group study for the design of a web-based tool for improving problem-solving in older adults. - Cipolletta, Sabrina; Signorello, Dario; Zuppiroli, Sara; Hering, Alexandra; Ballhausen, Nicola; Mioni, Giovanna; Kliegel, Matthias; Gaspari, Mauro; Stablum, Franca (European Journal of Ageing, 2024)
The development of easily accessible and usable social and cognitive enhancement trainings is becoming a priority to reduce the impact of aging on quality of life. Since most activities of daily living (e.g., making a meal) require problem-solving skills, problem-solving interventions could be used to improve and/or maintain functional abilities in aging to prolong independence. To design an effective problem-solving training and increase older adults' adherence to the training, this study examined older adults' perceptions of their challenges in activities of daily living, their skills and difficulties in using information technology (IT), and their motivations and expectations for participating in a web-based problem-solving training activity. Four focus groups (two in Italy and two in the Netherlands) were conducted with older adults aged between 65 and 84 years, a total of 27 participants. The data were analyzed using the Atlas.ti 8 software for the thematic analysis. The analysis identified five thematic areas: interests and activities, difficulties and concerns, experiences and motivations for training, expertise and resources, suggestions for the design of the new training. The results were used to develop a first prototype of a Shared, Web-based, Intelligent Flexible Thinking Training (SWIFT), adapted to future user needs. The participation of older adults in this design phase was critical to understanding their needs, motivations, and expectations regarding the implementation and use of a cognitive enhancement training.